2007
DOI: 10.5194/angeo-25-3-2007
|View full text |Cite
|
Sign up to set email alerts
|

Coincident extremely large sporadic sodium and sporadic E layers observed in the lower thermosphere over Colorado and Utah

Abstract: Abstract. On the night of 2 June 2002, the sodium lidar in Fort Collins, CO (40.6 N, 105 W) measured an extremely strong sporadic sodium layer lasting from 03:30 to 05:00 UT with several weaker layers later in the night at 06:00 and 09:00 UT. There is a double layer structure with peaks at 101 and 104 km. The peak sodium density was 21 000 atoms/cm3 with a column abundance of up to twice that of the normal sodium layer. The peak density was 500 times greater than the typical density at that altitude. The spora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 20 publications
3
35
0
Order By: Relevance
“…3). The sudden enhancements in Na density above ALOMAR around midnight during summer seem to differ from those observed during winter (see below) and those observed during summer at other sites (Williams et al, 2007). For this reason and because of their regular appearance, we avoid the term sudden sodium layer or sporadic sodium layer in this context similar to Friedman et al (2000).…”
Section: Summer Observationsmentioning
confidence: 99%
“…3). The sudden enhancements in Na density above ALOMAR around midnight during summer seem to differ from those observed during winter (see below) and those observed during summer at other sites (Williams et al, 2007). For this reason and because of their regular appearance, we avoid the term sudden sodium layer or sporadic sodium layer in this context similar to Friedman et al (2000).…”
Section: Summer Observationsmentioning
confidence: 99%
“…These observations showed much higher occurrence rates than those observed at mid-latitude before the 1990s. Williams et al (2007) suggested that this possibly indicates a large interannual or decadal variability in the sporadic layer occurrence rate.…”
Section: Introductionmentioning
confidence: 99%
“…More extensive studies on SSLs by lidars were conducted after the observation by Von Zahn and Hansen (1988) (e.g. Kwon et al, 1988;Batista et al, 1989;Senft et al, 1989;Kane et al, 1991;Gardner et al, 1993;Clemesha, 1995;Clemesha et al, 1998;Qian et al, 1998;Gong et al, 2002;Clemesha et al, 2004;Williams et al, 2006Williams et al, , 2007Fan et al, 2007;Nesse et al, 2008;Vishnu Prasanth et al, 2007;Yi et al, 2007;Heinrich et al, 2008). Sporadic sodium layers have been studied for more than 20 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies Clemesha et al, 1999;Williams et al, 2007;Dou et al, 2010;Xue et al, 2013] have shown that SSLs are associated with sporadic E (Es) layers. Cox and Plane [1998] reported that Na + can …”
Section: Sporadic E Layer Mechanismmentioning
confidence: 99%